Student Military Service Members' and Veterans' Experiences at University of Wisconsin-Eau Claire : Transitions, Support Systems, and Services - Bryant, Jason; Baumann, Irene; Ross, Rosalyn; Mateski, Katrina (My University, 2014)
The purpose of this study was to improve the current understanding of the transition from being a military service member to becoming a UWEC student, as well as the effects on their families. Another goal was to identify and improve UWEC campus support systems and services that are helpful for veteran students and families.
Color poster with text and images.
Keywords: Military to college; Student veterans; Posters